Polythiophene-Wrapped Olivine NaFePO4 as a Cathode for Na-Ion Batteries - Ali, Ghulam; Lee, Ji-Hoon; Susanto, Dieky; Choi, Seong-Won; Cho, Byung Won; Nam, Kyung-Wan; Chung, Kyung Yoon (American Chemical Society, 2016)
The surface of olivine NaFePO4 was modified with polythiophene (PTh) to develop a high-performance cathode material for use in Na-ion batteries. The Rietveld refinement results of the prepared material reveal that PTh-coated NaFePO4 belongs to a space group of Pnma with lattice parameters of a = 10.40656 angstrom, b = 6.22821 angstrom, and c = 4.94971 angstrom. Uncoated NaFePO4 delivers a discharge capacity of 108 mAh g(-1) at a current density of 10 mA g(-1) within a voltage range of 2.2-4.0 V. Conversely, the PTh-coated NaFePO4 electrode exhibits significantly improved electrochemical performance, where it exhibits a discharge capacity of 142 mAh g(-1) and a stable cycle life over 100 cycles, with a capacity retention of 94%. The NaFePO4/PTh electrode also exhibits satisfactory performance at high current densities, and reversible capacities of 70 mAh g(-1) at 150 mA g(-1) and 42 mAh g(-1) at 300 mA g(-1) are obtained compared with negligible capacities without coating. The related electrochemical reaction mechanism has been investigated using in situ X-ray absorption spectroscopy (XAS), which revealed a systematic change of Fe valence and reversible contraction/expansion of Fe O octahedra upon desodiation/sodiation. The ex situ X-ray diffraction (XRD) results suggest that the deintercalation in NaFePO4/PTh electrodes proceeds through a stable intermediate phase and the lattice parameters show a reversible contraction/expansion of unit cell during cycling.
Keywords: SODIUM-ION; ELECTROCHEMICAL PERFORMANCE; ELECTRODE MATERIALS; HIGH-CAPACITY; LITHIUM; LIFEPO4; PHOSPHATE; POLYPYRROLE; STABILITY; COMPOSITE